IMPLEMENTATION IMPACT OF LAW NO. 4 YEAR 2009 ON MINERAL AND COAL MINING TOWARDS MINERAL AND COAL BUSINESS DEVELOPMENT - DARSA PERMANA (Indonesian Mining Journal, 2010)
The issuance of Law No. 4 Year 2009 on Mineral and Coal Mining has certainly an impact on the manage- ment of mineral and coal mining operations throughout Indonesia as the law brings lots of new issues related to the regional autonomy that is contradictive to the previous issued regulation, i.e. Law No. 11 Year 1967 regarding centralized Main Guidelines on Mining. Surveys to several regions and business operation show that various problems have occurred. It needs early action to avoid bigger problems that will create a negative impact to the investment climate in mineral and coal mining sector, and will eventually hinder the improvement of people welfare.